Prisons 2000
XII, 269 p.
Keywords: A collection of original articles from a number of the world's leading authorities on imprisonment. The aim of the book is to review the current state of imprisonment around the world and to look at possible future developments. The underlying theme of the book is that imprisonment is undergoing a significant change in a number of different countries and that there are important lessons which can be learned from the analysis of these changes. At the same time this book is perceived as a 'state of the art' collection which provides an informed and comprehensive analysis of the major aspects of imprisonment. Consequently the book should be of interest to a wide-ranging international audience of academic researchers and policy-makers as well as students.